Understanding Factors Affecting Salespeople’s Perceptions of Ethical Behavior in South Africa - Abratt, Russell (Journal of business ethics, 2002)
Sales professionals have been frequent targets of ethical criticism. This paper reports on a survey on ethics of sales professionals in South Africa. The results revealed salespeople’s views on controversial sales practices that involve direct monetary consequences; on practices that adversely affect customers, employers and competitors; and on sales peoples sensitization of ethical issues. Stealing from a competitor at a trade show was viewed as the most unethical of the scenarios, while phone sabotage and lying to a customer were held to be the next most unethical scenarios. Analysis of the results lead to a discussion of the implications for sales management. Ethical perceptions were affected by financial considerations. Marketing and Sales Managers will have to review their approach to training in sales ethics as well as how sales professionals implement the market driven approach.